The API Model of Strategic and Tactical Marketing Thinking for Management Education - Martinović, Maja (International Review of Management and Marketing, 2024)
This paper addresses the need to improve marketing education for managers, particularly those from non-economic fields. Research indicates that effectively transferring marketing knowledge involves translating theory into practice, connecting with research, addressing diverse participant needs - relevance, and employing innovative working methods. The study was conducted on a sample of 142 MBA program participants from various non-economic backgrounds, who were presented with and explained the API (analysis, planning, implementation) model of strategic marketing thinking and tactical actions. The results show that visual presentation is a good method for displaying the connections in the model and can even change the perception of marketing. It is important to consider the participants’ prior knowledge of marketing since they show differences in the perceived clarity and usefulness of the model. After being introduced to the model, there are statistically significant differences in the changed perception of its clarity and usefulness among different groups based on their level of prior marketing knowledge. The findings suggest that the API model aids in comprehending environmental complexities and developing effective strategies and tactics, benefiting participants, employers, educators, and society overall.